2010
DOI: 10.1111/j.1095-8649.2010.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and characterization of embryonic stem‐like cells of Indian major carp Catla catla

Abstract: Embryonic stem (ES)-like cells were derived from mid-blastula stage embryos of a freshwater fish, catla Catla catla, under feeder-free condition and designated as CCES cells. The conditioned media was optimized with 10% foetal bovine serum (FBS), fish embryo extract (FEE) having 100 µg ml(-1) protein concentration, 15 ng ml(-1) basic fibroblast growth factor (bFGF) and basic media containing Leibovitz-15, DMEM with 4·5 g l(-1) glucose and Ham's F12 (LDF) in 2:1:1 ratio using a primary culture of CCES cells. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 68 publications
(97 reference statements)
1
22
0
Order By: Relevance
“…11,35,39 ZES1 colonies were strongly stained with AP, a common marker that has been used to positively identify pluripotency in zebrafish ES cells and other fish ES cell lines. [6][7][8][9]14,38 Our results also show how low-density culture condition induced the differentiation of ZES1 cells into neural and fibroblast cells, while muscle and epithelial cells appeared exclusively under high-density culture condition. ES cells isolated from several species, including medaka, sea bream, and sea perch, could also be directed to differentiate into neuronal or muscle-like cells when cultured in low and high density, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…11,35,39 ZES1 colonies were strongly stained with AP, a common marker that has been used to positively identify pluripotency in zebrafish ES cells and other fish ES cell lines. [6][7][8][9]14,38 Our results also show how low-density culture condition induced the differentiation of ZES1 cells into neural and fibroblast cells, while muscle and epithelial cells appeared exclusively under high-density culture condition. ES cells isolated from several species, including medaka, sea bream, and sea perch, could also be directed to differentiate into neuronal or muscle-like cells when cultured in low and high density, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…The medium composition was originally used to successfully derive several lineages of medaka ES cells and subsequently extended to the establishment of ES cell lines from other fish species. [6][7][8][9]11,25,35 A key difference between our tissue culture medium as compared with the previous unsuccessful formulations is the supplementation with zebrafish embryo extract. 22,26 It has been suggested that fish embryo extract contributes to the mitogenic activities of fish ES cell culture in a feeder-free culture system and could be a decisive addition in our present culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…. , , (Catla catla; Dash et al, 2010) (Oryzias dancena; Lee et al, 2013) 7 , (Lateolabrax japonicas; Chen et al, 2003a) (Chrysophrys major; Chen et al, 2003b) 36 , (Scophtalmus maximus, Holen and Hamre, 2003) 3 . , , (Collodi and Barnes, 1990;Na et al, 2009), (Assouline et al, 2002;Maures et al, 2002;Schimmang, 2007;Hanington et al, 2008), .…”
Section: 서 론 [Embryonic Stem Cells (Escs)]mentioning
confidence: 99%